A sociotoponímia em Minas Gerais - Emanoela Cristina Lima Cotta (2021)
Toponymy, a linguistic discipline that investigates the proper names of places, allows the recovery of aspects related to culture, history, language, customs and social activities carried out by a community. From the analysis of the toponyms, which make it possible to preserve the memory of a people, we will investigate the socio toponymic motivation in Minas Gerais. Sociotoponyms, according to the toponymic taxonomy model proposed by Dick (1990b, p. 34), are names of places linked to professional activities, places and workplaces and public places where people gather. The toponyms, object of study of this research, come from the database of the Atlas Toponymic Project of the State of Minas Gerais - ATEMIG, coordinated by Professor Maria Cândida Trindade Costa de Seabra. Of the more than 85 thousand toponyms collected by ATEMIG, 4133 place names are classified as sociotoponyms, which represents the fourth most recurrent anthropocultural taxonomy in the state. These data will, therefore, form the corpus of contemporary data from the work, which will also have another corpus of historical data, formed by sociotoponyms that named geographical accidents in the Captaincy of Minas Gerais in the 18th and 19th centuries, made available by the project's Cartographic Records Historical: revealing the Toponymic Heritage of Minas Gerais from the Colonial Period to Joanino. In this repository, there are 2500 historical toponyms, of which 48 have been classified as sociotoponyms. The two corpora will be analyzed based on the theoretical and methodological assumptions proposed by Dauzat (1926), Dick (1990a, 1990b) and Seabra (2004). The aim of this study is to describe the lexicon of this sociotoponymic of the territory of Minas Gerais. For this we highlight how social activities lead in the toponymic process of Minas Gerais. The history of the settlement of the state is intrinsically linked to the mining activity, which was decisive for the emergence and advancement of other activities such as agriculture, livestock, industry, from the Capitania das Minas, in 1720. Historical data revealed the predominance of names related to work, directly and indirectly linked to mining in the Captania. This prevalence was not maintained among contemporary data, since in this corpus there was a predominance of motivations related to agrarian activities. This change is historically confirmed by the decline of the mining activity, which transferred its prominence to agrarian activities, in particular, to cattle raising and coffee cultivation. This work also led us to the construction of a sociotoponymic glossary, with 862 entries. Furthermore, based on the most expressive motivations and the most productive sociotoponyms, we created eighteen toponymic letters. In addition to linguistic studies, therefore, our toponymic research also offers the possibility of historical investigation of Minas Gerais, based on sociotoponyms, in order to broaden the linguistic and cultural knowledge about the state.